An appraisal on serum preptin levels in polycystic ovary syndrome - Celik, O.; Hascalik, S.; Celik, N.; Sahin, I.; Aydin, S. (Oxford Univ Press, 2010)
[Abstract Not Available]
26th Annual Meeting of ESHRE -- JUN 27-30, 2010 -- Rome, ITALY